2018
DOI: 10.4314/bcse.v32i1.15
|View full text |Cite
|
Sign up to set email alerts
|

Efficientone-pot synthesis of imidazoles catalyzed by silica-supported La0.5Pb0.5MnO3 nano particles as anovel and reusable perovskite oxide

Abstract: ABSTRACT. Silica-supported La0.5Pb0.5MnO3 nanoparticles was prepared and used as a new perovskite-type catalyst for rapid and efficient synthesis of substituted imidazoles by an one-pot three-component condensation of [9,10]-phenanthraquinone, aryl aldehydes and ammonium acetate in excellent yield under reflux, and also solventfree conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…76 In particular, alternative approaches have been widely investigated to facilitate the removal and reuse of heterogeneous catalysts as well as the purification of the product. Some tested heterogeneous catalysts include magnetic nanoparticles, 77 heterogeneous silica-supported La 0.5 Pb 0.5 MnO 3 nanoparticles, 78 solid acids based on mercaptopropyl silica, 79 sulfamic acid (NH 2 SO 3 H), 80 ionic liquid-like phase catalyst based on Merrifield resin, 81 nanocatalysts, and SBAPr-SO 3 H incorporating propyl sulfonic acid groups. 82 Although progress has been made in the synthesis of phenanthro[9,10-d]imidazoles, the general approach of the condensation of phenanthrene-9,10-dione (13) with an aldehyde in the presence of ammonium acetate in acetic acid has been applied to prepare a set of fluorescent sensors for ionic and molecular recognition.…”
Section: ■ Synthesis Of Phenanthro[910-d]imidazolesmentioning
confidence: 99%
“…76 In particular, alternative approaches have been widely investigated to facilitate the removal and reuse of heterogeneous catalysts as well as the purification of the product. Some tested heterogeneous catalysts include magnetic nanoparticles, 77 heterogeneous silica-supported La 0.5 Pb 0.5 MnO 3 nanoparticles, 78 solid acids based on mercaptopropyl silica, 79 sulfamic acid (NH 2 SO 3 H), 80 ionic liquid-like phase catalyst based on Merrifield resin, 81 nanocatalysts, and SBAPr-SO 3 H incorporating propyl sulfonic acid groups. 82 Although progress has been made in the synthesis of phenanthro[9,10-d]imidazoles, the general approach of the condensation of phenanthrene-9,10-dione (13) with an aldehyde in the presence of ammonium acetate in acetic acid has been applied to prepare a set of fluorescent sensors for ionic and molecular recognition.…”
Section: ■ Synthesis Of Phenanthro[910-d]imidazolesmentioning
confidence: 99%
“…One year later, the same research group reported using heterogeneous silica-supported La 0.5 Pb 0.5 MnO 3 nanoparticles, prepared and used as a new Perovskite-type catalyst for the synthesis of imidazole derivatives (Scheme 15b). [50] Reactions were carried out under ethanol reflux, and the phenanthro [9,10-d]imidazole 73 was successfully obtained at 94 % yield. In neat conditions (absence of solvent), the product was obtained at 80 % yield.…”
Section: Phenanthro[910-d]imidazole and Phenanthro[910-d] Oxazolementioning
confidence: 99%
“…In the market, there are many drugs such as thiazole, thiophene, and pyridine derivatives. For such excessive benefits, these compounds were used in many efficient synthetic transformations and are used as intermediates in many chemical reactions . It has been reported that many thiazole, thiophene, and pyrazole derivatives showed potent analgesic, anticonvulsant, anti‐inflammatory and antibacterial, antipyretics, antitumor, antiparasitic, antimicrobial, antihistaminic, antianexiety test in mice, antiarrhythmic, and serotonin antagonist .…”
Section: Introductionmentioning
confidence: 99%